Public Policies and One Health in Brazil: The Challenge of the Disarticulation - Espeschit, Isis de Freitas; Santana, Clara Marques; Moreira, Maria Aparecida Scatamburlo (Frontiers in Public Health, 2021)
Working the One health strategy in developing countries is a challenge, due to structural weaknesses or deprivation of financial, human, and material resources. Brazil has policies and programs that would allow continuous and systematic monitoring of human, animal, and environmental health, recommending strategies for control and prevention. For animals, there are components of the Epidemiological Surveillance of zoonosis and Animal Health Programs. To guarantee food safety, there are Health Surveillance services and support of the Agropecuary Defense in the inspection of these products, productive environments, and their inputs. Environmental Surveillance Services monitor water and air quality, which may influence health. For human health, these and other services related to Health Surveillance, such as Worker Health and Epidemiological Surveillance, which has a training program responsible for forming professionals groups to respond effectively to emergencies in public health are available. Therefore, Brazil has instruments that may allow integrated planning and intervention based on the One Health initiative. However, the consolidation of this faces several challenges, such as insufficient resources, professional alienation, and lack of the recognition of the importance of animal and environmental health for the maintenance of human and planetary wellbeing. This culminates in disarticulation, lack of communication, and integration between organizations. Thus, efforts to share attributions and responsibilities must be consolidated, overcoming the verticality of the actions, promoting efficiency and effectiveness. Finally, this perspective aims to describe the government instruments that constitute potential national efforts and the challenges for the consolidation of the One Health initiative in Brazil.